Preliminary analysis of short-term real-world outcomes of telitacicept in high-risk IgA nephropathy - Ma, Ying; Han, Jing; Li, Huixian; Yu, Xiao; Lan, Ping; Xie, Xinfang; Lu, Wanhong; Sun, Jiping (Frontiers in Medicine, 2025)
IntroductionIgA nephropathy (IgAN) represents an important cause of end-stage kidney disease worldwide. Telitacicept has demonstrated potential in attenuating disease progression in IgAN patients. However, whether its efficacy differs between initial and alternative therapy in IgAN patients at high risk of kidney function progress (high-risk IgAN) remains unclear. This preliminary real-world study seeks to provide initial insights into this question.MethodsWe enrolled patients with primary IgAN who exhibited persistent proteinuria (≥ 0.75 g/day) and an estimated glomerular filtration rate (eGFR) ≥ 30 mL/min/1.73 m2 despite ≥ 3 months of supportive therapy. Participants receiving telitacicept as either initial or alternative treatment were propensity score-matched (1:1) based on baseline proteinuria and eGFR. A control group initiating conventional immunosuppressants (initial IS group) was included for comparison. Effectiveness endpoints included the renal response (RR) rate, defined as a complete (proteinuria < 0.5 g/day) or partial (>50% reduction and < 1 g/day in proteinuria) response, with both requiring stable renal function (eGFR decline ≤30%), as well as changes in proteinuria and eGFR from baseline during follow-up.ResultsA total of 138 patients were included in the full study cohort. After propensity score matching, ninety participants constituted the matched cohort, comprising 30patients in each of the three groups. At 3 months, the initial telitacicept group showed a median proteinuria reduction of 1.47 g/day (79% from baseline), comparable to the initial IS group (1.15 g/day, 48%) but significantly greater than the alternative telitacicept group (0.88 g/d, 46%). Concurrently, eGFR remained stable. 25 patients (83.3%) in the initial telitacicept group achieved RR-a rate significantly higher than in the other two groups. At 6 months, proteinuria in the initial telitacicept group continued to decline to 0.47 (0.20, 1.22) g/day, a level comparable to the initial IS group and numerically lower than the alternative telitacicept group. Throughout the follow-up, eGFR remained stable in the initial telitacicept group, whereas it exhibited greater fluctuation in the initial IS group. No serious adverse events were reported.ConclusionOur preliminary real-world findings suggest that telitacicept may be a safe and effective treatment for high-risk IgAN patients, significantly reducing proteinuria and preserving renal function. Its therapeutic benefits were more pronounced when used as initial therapy.